A Multimodal Comparative Analysis of Hurt in Nigerian Literature: Exploring Gender Differences in Linguistic, Stylistic, and Pragmatic Representations - Akpan, G. F. (Journal of Research in Adult and Continuing Education, 2025)
This study undertakes a multimodal comparative analysis of hurt in Nigerian literature in the work of Chinua Achebe’s Things Fall Apart (1979) and Buchi Emecheta’s The Joys of Motherhood (1979), exploring gender differences in linguistic, stylistic, and pragmatic representations investigating how male and female authors represent hurt and how these representations define, conform and/or challenge societal norms and values. This work relies on a mix theory of Trauma theory, stylistics, and post colonial theory. It uses a combination of Critical Discourse Analysis (CDA), stylistics, and pragmatic to investigate how hurt is constructed and conveyed in Nigerian literature and what these constructions reveal about gendered experiences, cultural norms, and power dynamics. Data was primary collected from the two novels under study. A qualitative and quantitative approach were used in the analysis. The findings reveal significant differences in how male and female authors represent hurt, with female authors employing more emotive language and stylistic devices to convey emotional pain, while make authors tend to use more direct and assertive language. The study also portrays the importance of considering the cultural and social context in which the texts were written, and how these contexts influence the representation of hurt. This work therefore is an addition to the field of literary linguistics, gender studies and African literature, providing new frontiers into the complex and multifaceted nature of hurt in Nigerian literature.